COMPOSITION OF SOILS OF BUKHARA REGION, THEIR AMENITIES (on the example of Jondor district) (International journal of artificial intelligence, 2024)
The article discusses the agricultural land areas of the Bukhara region, their improvement in productivity, land resources in the desert area, their reclamation, land reclamation, irrigation networks, land quality, crop rotation and obtaining high yields from them.